Ovid's toyshop of the heart : Epistulae heroidum - Verducci, Florence, 1940- (Princeton legacy library, 1985)
Florence Verducci challenges the presuppositions and expectations that have led to embarrassed censure of the wit and comic irreverence that Ovid wove into these dramatic monologues, addressed by his heroines to absent lovers. Originally published in 1986. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.